2022
DOI: 10.3390/rs14051170
|View full text |Cite
|
Sign up to set email alerts
|

Research on Shore-Based River Flow Velocity Inversion Model Using GNSS-R Raw Data

Abstract: Global navigation satellite system reflectometry technology (GNSS-R) is rarely used for river flow velocity inversion, and in particular, there is currently no research using the BeiDou Navigation Satellite System reflectometry technology (BDS-R) for river flow velocity inversion. In this paper, a carrier phase observation of river flow velocity inversion model is proposed. The interference phase is the integral of the Doppler frequency. The raw intermediate frequency (IF) data sets are processed through an op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…River flow velocity is fundamental in hydrologic studies, and its detection is valuable for the reason that it links variables such as hydrologic detection, flood control engineering design, hydrologic prediction, ecological environment assessment, and hydrodynamic research (Eric et al, 2021). The potential of the GNSS-R application in river flow measurement was studied using the Chinese BDS constellation (Zhang et al, 2022a(Zhang et al, , 2022b. A river flow velocity retrieval model, based on carrier phase observations, was developed to include both openloop tracing and the carrier phase streamflow retrieval method.…”
Section: River Flowmentioning
confidence: 99%
“…River flow velocity is fundamental in hydrologic studies, and its detection is valuable for the reason that it links variables such as hydrologic detection, flood control engineering design, hydrologic prediction, ecological environment assessment, and hydrodynamic research (Eric et al, 2021). The potential of the GNSS-R application in river flow measurement was studied using the Chinese BDS constellation (Zhang et al, 2022a(Zhang et al, , 2022b. A river flow velocity retrieval model, based on carrier phase observations, was developed to include both openloop tracing and the carrier phase streamflow retrieval method.…”
Section: River Flowmentioning
confidence: 99%
“…Based on particle tracking velocimetry, Eltner et al [ 4 ] collected and estimated River images. The results show that the deviation of this method is between 4% and 5% [ 4 ]; Zhang et al [ 5 ] used the reflection technology of BeiDou system to inverse the river velocity and then obtained the river velocity with small error [ 5 ].…”
Section: Related Workmentioning
confidence: 99%
“…In view of the above problems, some scholars also proposed to process the collected water flow images. For example, Gulrajani et al [ 6 ] proposed to introduce gradient punishment mechanism into the WGAN algorithm to better improve the WGAN algorithm [ 5 ]. David proposed an image processing technology based on the BEGAN algorithm to solve the contradiction between picture type and generation [ 6 ].…”
Section: Related Workmentioning
confidence: 99%
“…In terms of river flow detection, Warnock et al used CYGNSS IF data to define the correlation width of time delay waveform inverts the flow of the Mississippi River and finds that Associated GNSS-R Width (AGW) is proportional to the flow of the river, demonstrating the feasibility of space-borne GNSS-R detecting the flow of the river [25]. In terms of velocity detection, literature [26][27][28] all found that GNSS signals reflected by flow surface had a small Doppler deviation compared with direct signals, which was related to fluid velocity. All these indicate that GNSS-R technology has certain potential in river detection.…”
Section: ⅰ Introductionmentioning
confidence: 99%